2016
DOI: 10.1016/j.jad.2015.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state functional network connectivity in prefrontal regions differs between unmedicated patients with bipolar and major depressive disorders

Abstract: Background Differentiating bipolar disorder (BD) from major depressive disorder (MDD) often poses a major clinical challenge, and optimal clinical care can be hindered by misdiagnoses. This study investigated the differences between BD and MDD in resting-state functional network connectivity (FNC) using a data-driven image analysis method. Methods In this study, fMRI data were collected from unmedicated subjects including 13 BD, 40 MDD and 33 healthy controls (HC). The FNC was calculated between functional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 85 publications
4
44
0
Order By: Relevance
“…Abnormal medial prefrontal cortex connectivity between ICA components were also found during the resting-state in the BD group in multiple previous studies (Calhoun et al 2011; Ongur et al 2010). Our findings with stronger FC in BD subjects within the prefrontal cortical areas highlighted in Module 1 not only replicated our recent results on the same dataset with different analysis approaches (He et al 2016), but also are in line with prior resting-state FC studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Abnormal medial prefrontal cortex connectivity between ICA components were also found during the resting-state in the BD group in multiple previous studies (Calhoun et al 2011; Ongur et al 2010). Our findings with stronger FC in BD subjects within the prefrontal cortical areas highlighted in Module 1 not only replicated our recent results on the same dataset with different analysis approaches (He et al 2016), but also are in line with prior resting-state FC studies.…”
Section: Discussionsupporting
confidence: 92%
“…The magnitude (absolute value) of functional network connectivity strength was used as the fMRI data feature to input into the multimodal fusion analysis. For more details of FNC feature generation, please refer to our previous publication (He et al 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These have included whole-brain ICA studies, in which the interactions or spatial extent of major large-scale networks have been investigated (35, 61, 62). Importantly, some of these studies revealed findings compatible with the data previously reviewed, including alterations in left vlPFC/opercular regions (61), reduced interactions between right dlPFC- and amygdala/striatum-related independent components (35), and heightened connectivity between medial and lateral PFC subregions (63). By replicating similar networks to seed based studies, such findings also provide important validation of previous work, given that they may be less susceptible to bias.…”
Section: Global Network Approachessupporting
confidence: 79%
“…automated anatomical labeling, AAL template) to define the nodes based on brain structure. Alternatively, independent component analysis (ICA) can be run to detect independent components (ICs, spatial brain maps), which can be considered as graph nodes (He et al, 2016; Smith, 2012; Smith et al, 2011; Yu et al, 2015; Yu et al, 2011a; Yu et al, 2013a; Yu et al, 2013b; Yu et al, 2011b; Yu et al, 2016). While the “correct” method for defining the brain nodes remains an open question that deserves further extensive research (Stanley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%